Entre o convencional e o digital: o assentamento funcional como informação arquivística - DIOGO, Benedita Cristina Amaral (2018)
It presents a Literature Review, focusing on Digital Functional Settlement (AFD), a database that is treated as the primary source of information. It raises issues related to this repository in aspects such as: digitalization, access and digital preservation. It uses the Content Analysis method to demonstrate how AFD is being implemented in 29 Brazilian federal universities, in which 61% of the universities surveyed already use this digital repository. It relates in this analysis to the statements of the actors involved (the universities) and to the legal provisions, such as Ministerial Order No. 4/2016 and Law 12,527 / 2011. It contributes as a research source, given the lack of material for an extensive bibliographic study that addresses this issue, serving as the basis for future research.